Words Come Alive: Benefits and Barriers of the Reading Aloud Strategy to Young Readers - Rachmatia, Meutia; Hamzah, Intan; Wengrum, Tyas Desita; Nurhartanto, Adhi (Faculty of Arts and Education, 2024)
AbstractThis study examines the benefits and barriers of implementing the Reading Aloud strategy for young readers, particularly at the elementary school level. Through a theoretical research approach, we analyze recent literature and studies from 2019-2023 to provide a comprehensive understanding of how this strategy shapes early literacy development. The research highlights the multifaceted benefits of Reading Aloud, including enhanced vocabulary acquisition, improved comprehension skills, increased fluency and prosody, and the fostering of critical thinking abilities. These advantages are grounded in established educational theories such as Vygotsky's Zone of Proximal Development and Bandura's Social Learning Theory. However, the study also identifies several barriers to effective implementation, including time constraints, the need for proper training, and the challenge of selecting appropriate reading materials. The paper discusses strategies to overcome these obstacles and explores the potential of integrating modern technologies to enhance this fundamental literacy practice. By synthesizing current research and analyzing emerging trends, this study offers valuable insights for educators, parents, and policymakers striving to nurture a new generation of literate and engaged readers. The findings underscore the continued relevance and effectiveness of the Reading Aloud strategy in contemporary educational settings, supporting its implementation as a versatile tool for literacy instruction across various learning environments. Keywords: Educational strategies, elementary education, literacy development, reading aloud, young readers.